2018
DOI: 10.3390/catal8040130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Iron Vanadates for Simultaneous Carbon Soot Abatement and NH3-SCR

Abstract: FeVO 4 and Fe 0.5 Er 0.5 VO 4 were prepared and loaded over standard Selective Catalytic Reduction (SCR) supports based on TiO 2 -WO 3 -SiO 2 (TWS) and redox active supports like CeO 2 and CeZrO 2 with the aim of finding a suitable formulation for simultaneous soot abatement and NH 3 -SCR and to understand the level of interaction between the two reactions. A suitable bi-functional material was identified in the composition FeVO 4 /CeZrO 2 where an SCR active component is added over a redox active support, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The reducibility of vanadia appears to be deteriorated with the peak temperature shifting to 560 °C, which is probably due to the chemical transformation of monomeric vanadia to less active vanadate species. 44 A new notable peak at 660 °C may be attributed to the reduction of formed tungstate solid solutions after the aging of SCR catalyst with cement dust, which was in accordance with the XPS analysis (shown in Figure 5B). According to the previous reports, the easy oxidation− reduction conversion of active sites such as V 5+ /V 4+ will promote the NH 3 -SCR reaction with high DeNO x efficiency.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 83%
“…The reducibility of vanadia appears to be deteriorated with the peak temperature shifting to 560 °C, which is probably due to the chemical transformation of monomeric vanadia to less active vanadate species. 44 A new notable peak at 660 °C may be attributed to the reduction of formed tungstate solid solutions after the aging of SCR catalyst with cement dust, which was in accordance with the XPS analysis (shown in Figure 5B). According to the previous reports, the easy oxidation− reduction conversion of active sites such as V 5+ /V 4+ will promote the NH 3 -SCR reaction with high DeNO x efficiency.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 83%
“…It is remarkable that the systems for NO x and soot elimination analyzed individually are efficient in each technology, and the studies concerning the simultaneous removal are mainly focused on the reduction of the storage capacity due to the presence of soot that competes for the active centers. For SCR materials, few studies involving soot can be found, but the SDPF system is emerging and consists of an NH 3 –SCR catalyst coated onto a wall-flow DPF. Therefore, the NO x removal catalysts are not real soot combustion materials but can be affected by the presence of soot on the surface since it is not completely reduced in the DOC or DPF device. Soot covers the catalysts and has to be oxidized using the materials as passive converters of soot.…”
Section: Introductionmentioning
confidence: 99%
“…The Fig.1 depicts the powder X-ray diffraction (PXRD) pattern of prepared iron vanadate nanoparticles. The recorded PXRD patterns was matched with JCPDS card number 71-1592 and indexed with hkl planes [11,[9][10][11][12][13][14][15][16][17][18][19][20]. The structure obtained was found to be primitive with cell parameters a=6.719 b=8.060 c=9.254 and α=96.6, β=106.57, γ=101.60.…”
Section: A Pxrdmentioning
confidence: 99%
“…In connection with this, iron vanadate has various merits including its availability in nature, low toxicity, chemical stableness and user friendly in fabrication process. A wide variety of iron vanadate had been synthesized and investigated as they possess various application [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%